Effect of nonelectrolytes and tonicity on hydrosmotic properties of toad bladder - Nogueira Silveira, J. E.; Cirne, B.; Malnic, G. (My University, 1975)
Water flow was measured gravimetrically in toad bladder sacs incubated in solutions of different ionic content. Substitution of Ringer's solution by isotonic and hypertonic nonelectrolyte solution increases water permeability markedly and depresses the effect of ADH on this structure. This effect is not reversible returning to Ringer after a preincubation for 3 hours in these solutions. It is also found, to a lesser extent, in Ringer made hypertonic with NaCl. Such effects are prominent when nonelectrolyte solutions are applied to the serosal medium; when applied to the mucosal side only, isotonic nonelectrolyte solutions do not induce alterations in water permeability, while the effect of hypertonic solutions is delayed. In nonelectrolyte solutions, the addition of calcium tends to normalize water permeability, but not ADH action. The addition of potassium has no effect on either function. On the other hand, a normal water permeability can be maintained when up to 50% of Ringer's solution is substituted by 400 mM mannitol. These findings indicate that an adequate ionic content of its fluids is necessary for the preservation of the hydrosmotic function of the toad bladder, and that this epithelium appears to be more sensitive to electrolyte depletion via its serosal cell membrane than across the mucosal border.